Majority judgment: Measuring, ranking, and electing - Balinski, Michel; Laraki, Rida (London The MIT Press, 2010)
In Majority Judgment, Michel Balinski and Rida Laraki argue that the traditional theory of social choice offers no acceptable solution to the problems of how to elect, to judge, or to rank. They find that the traditional model$1 (Btransforming the "preference lists" of individuals into a "preference list" of society$1 (Bis fundamentally flawed in both theory and practice. Balinski and Laraki propose a more realistic model. It leads to an entirely new theory and method$1 (Bmajority judgment$1 (Bproven superior to all known methods. It is at once meaningful, resists strategic manipulation, elicits honesty, and is not subject to the classical paradoxes encountered in practice, notably Condorcet's and Arrow's.s
Keywords: Social choice; Voting; Ranking and selection (Statistics)